Post cholecystectomy pancreatitis: a misleading entity - Vagholkar, Ketan; Pawanarkar, Amish; Vagholkar, Suvarna; Pathan, Shamshershah; Desai, Rohini (International Surgery Journal, 2016)
Cholecystectomy is one of the commonest hepatobiliary procedures performed in general surgical practice. Both laparoscopic as well as open cholecystectomies have their place in modern-day surgical practice. Post cholecystectomy syndrome is a known entity affecting approximately 20% of patients who have undergone cholecystectomy. Post cholecystectomy pancreatitis is an uncommon and rare complication. A case of acute early post cholecystectomy pancreatitis is presented to create an awareness of this rare but misleading and morbid complication.